Behavioural Decision Theory and the Gains Debate in International Politics. - Mulford, Matthew; Berejikian, Jeffery (Political Studies, 2002)
The temptation to free ride and the fear of exploitation are traditionally offered as factors explaining individuals’ choices under conditions of social dilemma. In two experimental studies of prisoner’s dilemma behaviour we demonstrate that the ratio-differences of payoffs are as important as the absolute differences in affecting the likelihood of cooperation. The implications of this additional structural determinant of dilemma choice are developed and applied to the stalled gains debate in international relations theory. By incorporating ratio-differences into the analysis ‘realist’ and ‘liberal’ theories of state behaviour may be reconciled.